Sequence and expression of myoglianin, a novel Drosophila gene of the TGF-beta superfamily - Lo, Patrick CH; Frasch, Manfred (Mechanisms of Development, 1999)
Various members of the TGF-beta superfamily of signaling molecules are known to have important roles in mesoderm patterning and differentiation during vertebrate and invertebrate embryogenesis. Here we characterize a new TGF-beta member from Drosophila, Myoglianin, that is most closely related to the vertebrate muscle differentiation factor Myostatin and to vertebrate BMP-11. Northern analysis shows that myoglianin is expressed throughout the Drosophila life cycle. In situ hybridization detects maternally-derived transcripts that are enriched in the pole plasm and later become enclosed in the pole cells. Between stares 11 and 14, myoglianin mRNA is exclusively detected in glial cells and their precursors. Following stage 14, high levels of myoglianin expression are observed in the developing somatic muscles as well as in visceral muscles and cardioblasts. We also show that the zygotic expression of a recently described Drosophila activin, which maps to the same interval 102 on chromosome 4 as myoglianin, is restricted to the developing central and peripheral nervous system. (C) 1999 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Drosophila; TGF-beta; bone morphogenetic proteins; myostatin; muscles; glia